Prospective study of healthcare utilisation and respiratory morbidity due to RSV infection in prematurely born infants. Issue 12 (14th October 2005) - Broughton, S; Roberts, A; Fox, G; Pollina, E; Zuckerman, M; Chaudhry, S; Greenough, A
Abstract : Background: A study was undertaken to determine the impact of respiratory syncytial virus (RSV) infection, both in hospital and the community, on healthcare utilisation and respiratory morbidity in prematurely born infants and to identify risk factors for symptomatic RSV infection. Methods: A hospital and community follow up study was undertaken of 126 infants born before 32 weeks of gestational age. Healthcare utilisation (hospital admissions and general practitioner attendances) in the first year, respiratory morbidity at follow up (wheeze and cough documented by parent completed diary cards), and RSV positive lower respiratory tract infections (LRTIs) were documented. Nasopharyngeal aspirates were obtained for immunofluorescence and culture for RSV whenever the infants had an LRTI, either in the community or in hospital. Results: Forty two infants had an RSV positive LRTI (RSV group), 50 had an RSV negative LRTI (RSV negative LRTI group), and 32 infants had no LRTI (no LRTI group). Compared with the RSV negative LRTI and the no LRTI groups, the RSV group required more admissions (p = 0.392, p<0.001) and days in hospital (p = 0.049, p = 0.006) and had more cough (p = 0.05, p = 0.038) and wheeze (p = 0.003, p = 0.003) at follow up. Significant risk factors for symptomatic RSV LRTI were number of siblings (p = 0.035) and maternal smoking in pregnancy (p = 0.005), for cough were number of siblings (p = 0.002) and RSV LRTI (p = 0.02), and for wheeze was RSV LRTI (p = 0.019). Conclusion: RSV infection, even if hospital admission is not required, is associated with increased subsequent respiratory morbidity in prematurely born infants.